(untitled) (Bangladesh Journal of Botany, 2015)
Morphological, anatomical and palynological properties of Cyclamen mirabile Hildebr. endemic to Anatolia, Turkey have been determined. Typifications, synonym lists, descriptions, ecology and phytogeography are provided for the species and its relationships to similiar species are discussed. The anatomical study from different plant parts of C. mirabile have been made for the first time. Its pollen morphologies were also defined. Morphological findings obtained in the present investigation were generally consistent with those given in the Flora of Turkey with some exceptions in numerical data. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21589 Bangladesh J. Bot. 43(3): 243-247, 2014 (December)